Hubungan Tingkat Ekonomi Keluarga dengan Pemilihan Arah Karir Peserta Didik di SMA Negeri 1 Sitiung - Melisa Febriani; Besti Nora Dwi Putri; Citra Imelda Usman (Journal on Education, 2023)
This study entitled The Relationship between Parents' Economic Level and Students' Career Direction Selection. This study aims to determine: 1) The economic level of the parents of students at SMA Negeri 1 Sitiung. 2) Selection of the career direction of students at SMA Negeri 1 Sitiung. 3) The relationship between the economic level of parents and the career direction of students at SMA Negeri 1 Sitiung. This type of research is a quantitative descriptive with a correlational approach. The population of this study were students at SMA Negeri 1 Sitiung, totaling 147 students. The sampling technique was carried out using simple random sampling technique, namely as many as 108 students who became the research sample. The data analysis technique of this study used descriptive statistics, data analysis was carried out after the data was collected through a questionnaire. Furthermore, the prerequisite analysis test of this study used the normality test and data linearity test. The results of this study indicate: 1) The economic level of the parents of students at SMA Negeri 1 Sitiung is in the very high category. 2) Selection of the career direction of students at SMA Negeri 1 Sitiung is in the high category. 3) There is no relationship between the economic level of parents and the career direction of students at SMA Negeri 1 Sitiung with a very low coefficient.